Direct measurement of superdiffusive energy transport in disordered granular chains - Eunho Kim; Alejandro J. Martínez; Sean E. Phenisee; P. G. Kevrekidis; Mason A. Porter; Jinkyu Yang (Nature Communications, 2018)
Wave propagation is often nonlinear in character, yet the interplay between disorder and nonlinearity remains elusive. Kim et al. use experiments and corroborating numerical simulations to investigate this phenomenon and demonstrate superdiffusive energy transport in disordered granular chains.